DAILY OCCUPATIONS OF DAGESTAN UZDENIS IN THE SECOND HALF OF THE 19th – EARLY 20th CENTURIES - Dalgat, El'mira Murtuzalievna (History, Archeology and Ethnography of the Caucasus, 2022)
The subject of this research is the daily activities of Dagestan freemen (commoners) – uzdenis in the second half of the 19th – early 20th century. In our research, we have applied procedural and modernization approaches. The first approach considers everyday life as an ordinary, everyday human existence, focusing on the environment, social relations in society. The modernization approach considers the transition of society from the traditional to the modern type, accompanied by the breaking of traditional values, a change in mentality. The article applies historical-genetic and historical-comparative methods. The author describes for the first time the daily activitis of Dagestan uzdenis after the annexation of Dagestan to Russia. The article aims to show the changes that occured in the traditional occupation of Dagestan uzdenis under the influence of capitalist relations that came from the Russian Empire. The author concludes that the daily occupations of the Dagestan freemen comprised traditional forms of agricultural production. The basis of the labor activity of uzden farms was the economic experience of previous generations. Farming in different parts of Dagestan had its own peculiarities. It received special development in the flat and foothill parts of the region with more arable land. In the mountainous zone, the lack of arable land forced farmers to use artificial fields – terraces created and maintained by the labor of several generations. Terraces testify to a high agriculture and have a centuries-old history in Dagestan. In addition to agriculture, Dagestani uzdenis were engaged in cattle breeding, handicrafts, seasonal work, and fishing. A major role in the daily activities of Dagestanis was played by the natural and climatic factor, which dictated the timing of agricultural work. Thus, in the second half of the 19th – early 20th century, the usual way of daily life of the Dagestan peasant gradually changed. Agriculture and cattle breeding acquired a commodity character, factory-made agricultural tools appeared on the farms of wealthy peasants, and the geography of seasonal works expanded. This might be explained by the integration of Dagestan into the economic space of Russia and the modernization of its economy during the period under study.